Pengaruh Nisbah Kelamin Perkawinan Terhadap Litter Size dan Jumlah Anak Perkandang Perkawinan Tikus Putih Wistar - Taofik, Ahmad; Depison, Depison (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2008)
This research was conducted to know the influence of sex ratio parental on pregnant females, litter size and output per breed of white wistar rat. Experiment started on January 1st – March 10th, 2008. This experiment sample was taken from  PAU Institute Teknology Bandung and it done at Garden of Botany of  Faculty  of  Mathematics  and  Natural  Sciences  of  University  of  Education  Indonesia.  As  many  128 white  wistar  rat  consisted  of  112  females  mating  old  (virgin)  with  body  weight  162-235  gram  and  16 males  mating  old  with  body  weight  275-325  gram  placed  randomly  into  cage  60  cm  x  40  cm  x  25  cm. This research was used experiment methode with Completely Randomized Design (CRD). The treatment, were R1 =  1 : 4 (1 male and 4 females), R2 = 1 : 6 (1 male and 6 females),    R3 = 1 : 8 (1 male and 8 females) dan R4= 1 : 10 (1 male and 10 females). The placement was according to treatment group and each treatment repeated four times. Males and females oestrus kept together until five days, account the pregnant females, litter size, and output per breed of white wistar rat. Analysis of Variance was used to analyse the  data.  The  result  of  this  research  indicated  that  sex  ratio  not  significantly  (P  >  0,05)  on pregnant females, litter size and output per breed of white wistar rat.